2019
DOI: 10.1038/s41598-019-38575-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Epidermal Growth Factor Receptor (EGFR) and Human Epidermal Growth Factor Receptor 2 (HER2) Expressing Bladder Cancer Using Combination Photoimmunotherapy (PIT)

Abstract: Bladder cancer (BC) is heterogeneous and expresses various cell surface targets. Photoimmunotherapy (PIT) involves monoclonal antibodies (MAbs) conjugated to a photoabsorber (PA), IR Dye 700Dx, and then activated by near infra-red light (NIR) to specifically target tumors. We have demonstrated that tumors expressing EGFR can be targeted with PIT. However, PIT may be less effective when a tumor lacks “overwhelming” expression of a single target such as EGFR. We present a combinatorial PIT approach for targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 30 publications
4
50
0
Order By: Relevance
“…NIR-PIT using HER2 Affibody–IR700Dye conjugate has a real therapeutic potential for brain metastases of HER2-overexpressing cancers. Lastly, NIR-PIT using mAb to target HER2 protein is already reported for ovarian cancer, gastric cancer, bladder cancer, as well as breast cancer [5,6,7,29,33]. HER2 Affibody–IR700Dye conjugate can also target these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…NIR-PIT using HER2 Affibody–IR700Dye conjugate has a real therapeutic potential for brain metastases of HER2-overexpressing cancers. Lastly, NIR-PIT using mAb to target HER2 protein is already reported for ovarian cancer, gastric cancer, bladder cancer, as well as breast cancer [5,6,7,29,33]. HER2 Affibody–IR700Dye conjugate can also target these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Panitumumab-IR700- and trastuzumab-IR700-mediated combination PIT therapy has a higher cytotoxicity to human bladder tumor cell lines (e.g., SW780) and a stronger anti-tumor effect in bladder tumor xenograft models than either single agent. 30 In another study, anti-CD47-IR700-mediated PIT increased cytotoxicity to human bladder tumor cell lines and primary bladder tumor cells significantly in a light dose-dependent manner. Compared with the NIR irradiation group and blank control group, the tumor growth rate in the NIR-PIT group was significantly decreased.…”
Section: Main Textmentioning
confidence: 94%
“…The therapeutic epidermal growth factor receptor (EGFR) monoclonal antibodies cetuximab and panitumumab, and the human EGFR-2 (HER-2) antibody trastuzumab, after binding to IRDye 700DX (IR700), have been used in PIT of BC management. 29 , 30 , 31 However, fluorophore-antibody conjugate-based optical molecular imaging has some recognized limitations, such as the long half-life of blood circulating and poor penetration into tumor tissue due to its large molecular size (150 kDa). 32 Furthermore, due to nonspecific tissue accumulation of molecular tracer by the enhanced permeability and retention (EPR) effect, the added clinical value of fluorescence-guided surgery (FGS) will be discounted by false-positive results and lower tumor-to-background ratio (TBR) signals.…”
Section: Main Textmentioning
confidence: 99%
“…In vivo specific A431 (epidermoid) and 3T3/HER2 (breast) tumor accumulation and shrinkage were initially reported (300 µg/mouse, DLI = 24 h, DL = 30 J/cm 2 ) [ 142 ]. This strategy was further investigated for bladder cancer treatment, either in monotherapy with panitumumab-targeted IR700 [ 143 ] or upon combination of the latter with trastuzumab (anti-HER2)-targeted IR700 [ 144 ]. Additional works have demonstrated that this strategy can be effective for tumors of different histological origin by using antibodies against relevant targets.…”
Section: Ligand-targeted Photosensitizersmentioning
confidence: 99%
“…Overall, mAb-IR700 has the ability to induce specific cell death of cancer cells while sparing adjacent healthy tissue, tumor vessels and infiltrating-immune cells [ 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 ]. The mechanism triggering necrotic cell death was recently highlighted by Sato et al [ 151 ].…”
Section: Ligand-targeted Photosensitizersmentioning
confidence: 99%